Prevalence and Risk Factors of Hearing Loss in Children in Mumbai, India - Singh, Sharma (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Hearing loss (GP) is a significant public health problem in India, especially in children. In Mumbai, the prevalence of GP among children is not yet known with certainty. This study aims to determine the prevalence and risk factors of GP in children in Mumbai. Methods: This research was conducted cross-sectionally involving 500 children aged 5-15 years in Mumbai. Data was collected through interviews and hearing examinations. Risk factors analyzed included age, gender, socioeconomic status, noise exposure, and history of ear infections. Results: The prevalence of GP among children in Mumbai is 12%. Risk factors significantly associated with GP were age, noise exposure, and history of ear infections. Conclusion: The prevalence of GP among children in Mumbai is quite high. The main risk factors for GP are age, noise exposure, and history of ear infections. Efforts to prevent GP in children in Mumbai need to focus on controlling noise exposure and treating ear infections early.